Analisis Kandungan Fenol, Flavonoid, dan Aktivitas Antioksidan Ekstrak Kurma (Phoenix dactylifera L.) - Andriani, Silvia; Sulistianingsih, Apri; Puspa, Egita Windrianatama; Sahroni, Mizan; Suharyani, Suharyani; Susanto, Syifaun Nafiah; Febriana, Tyas (Fakultas Kedokteran Universitas Riau, 2024)
Air pollution and shifts in consumption habits toward more immediate choices have negatively impacted health by increasing the levels of free radicals in the body. Antioxidants, which can neutralize free radicals, are found in various plants, including dates (Phoenix dactylifera L.). Dates are known to exhibit antioxidant properties. In this study, date fruits were extracted using distilled water as a solvent through the maceration method, followed by evaporation. The resulting extract was subjected to qualitative secondary metabolite testing, alongside analyses for total phenolic and flavonoid content, as well as antioxidant activity using the DPPH method with UV-Vis spectrophotometry. The data were analyzed by calculating the inhibition concentration 50 (IC50) value, and results were fitted into a regression equation. Phytochemical tests confirmed the presence of alkaloids, flavonoids, and tannins in the date extract. The antioxidant activity test yielded an IC50 value of 98.02 µg/ml, classifying the extract as having very strong antioxidant activity. The total phenolic content was 1.16 mg GAE/g extract, and the total flavonoid content was 0.12 mg QE/g extract, indicating that the date extract contains significant levels of phenolic and flavonoid compounds.